Is sedentary behavior an intervening factor in the practice of physical activity in the elderly? - Oliveira, Daniel Vicentini de; Lima, Maria do Carmo Correia de; Oliveira, Gustavo Vinicius do Nascimento de; Bertolini, Sônia Maria Marques Gomes; Nascimento Júnior, José Roberto Andrade do; Cavaglieri, Cláudia Regina (Revista brasileira de geriatria e gerontologia, 2018)
Abstract Objective: the present study aimed to analyze the association between current sedentary behavior and the practice of physical activity among elderly persons in the city of Maringá in the state of Paraná. Method: a cross-sectional study of 970 elderly subjects was carried out, using the International Physical Activity Questionnaire. Results: the modeling of structural equations revealed that the sedentary behavior has a significant effect (p <0.05) on the activities moderate and vigorous activities, explaining 3% and 4% of the variability of these variables. Specifically, it has been found that increased sedentary behavior has a (β = 0.13) and negative on vigorous activities (β = -0.21). Conclusion: the current state of sedentary behavior has a significant effect on moderate and vigorous activities. Resumo Objetivo: este estudo teve como objetivo analisar a associação do comportamento sedentário atual na prática de atividade física de idosos da cidade de Maringá-PR. Método: estudo transversal, realizado com 970 idosos. Foi utilizado o International Physical Activity Questionnaire. Resultados: a modelagem de equações estruturais revelou que o comportamento sedentário tem um efeito significativo (p < 0,05) sobre as atividades moderadas e atividades vigorosas, explicando 3% e 4% da variabilidade destas variáveis. Especificamente, verificou-se que o aumento do comportamento sedentário tem efeito positivo sobre as atividades moderadas (β = 0,13) e negativos sobre as atividades vigorosas (β = -0,21). Conclusão: o estado de comportamento sedentário atual tem efeito significativo sobre as atividades moderadas e atividades vigorosas.